THE TERM OF PRAGMATICS IN LINGUISTICS - Alimova Gulnazkhon Yuldashaliyevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: The article discusses the theory of how pragmatic competence occurs and includes the classification patterns of speech acts.